2020
DOI: 10.3390/microorganisms8081253
|View full text |Cite
|
Sign up to set email alerts
|

Host–Pathogen Interactions between Xanthomonas fragariae and Its Host Fragaria × ananassa Investigated with a Dual RNA-Seq Analysis

Abstract: Strawberry is economically important and widely grown, but susceptible to a large variety of phytopathogenic organisms. Among them, Xanthomonas fragariae is a quarantine bacterial pathogen threatening strawberry productions by causing angular leaf spots. Using whole transcriptome sequencing, the gene expression of both plant and bacteria in planta was analyzed at two time points, 12 and 29 days post inoculation, in order to compare the pathogen and host response between the stages of early visible and of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 114 publications
1
8
1
Order By: Relevance
“…The complete list of identified and annotated transcripts is provided as Supplementary Table S3 . The number of identified genes from S. subterranea in this study exceeded what has been reported in other in planta transcriptome analysis of plant pathogens [ 12 , 26 , 27 ]. According to the hierarchical clustering (sample-to-sample distances) of all six samples ( Figure 2 A) and principal component analysis (PCA) ( Figure 2 B), our RNA-seq approach was sensitive enough to capture S. subterranea transcriptome differences between the biological replicates.…”
Section: Resultscontrasting
confidence: 42%
“…The complete list of identified and annotated transcripts is provided as Supplementary Table S3 . The number of identified genes from S. subterranea in this study exceeded what has been reported in other in planta transcriptome analysis of plant pathogens [ 12 , 26 , 27 ]. According to the hierarchical clustering (sample-to-sample distances) of all six samples ( Figure 2 A) and principal component analysis (PCA) ( Figure 2 B), our RNA-seq approach was sensitive enough to capture S. subterranea transcriptome differences between the biological replicates.…”
Section: Resultscontrasting
confidence: 42%
“…Indeed, most transcriptomic studies in Xcc or other Xanthomonas species have so far been performed in vitro focusing on specific regulons of the hrpG and hrpX genes in hrp‐ inducing media, of the prc protease gene, of the DSF‐mediated quorum‐sensing system, or of the gum genes responsible for xanthan production (Alkhateeb et al, 2016 ; An et al, 2014 ; Chen et al, 2018 ; Jalan et al, 2013 ; Kim et al, 2016 ; Li et al, 2019 ; Liao et al, 2016 ; Liu et al, 2013 ; Noh et al, 2016 ; Schmidtke et al, 2012 ; Zhang et al, 2013 ). Only a few in planta transcriptomic analyses have been performed on Xanthomonas (Getaz et al, 2020 ; Lee et al, 2017 ; Li et al, 2019 ; Liao et al, 2019 ) and all at late stages of infection and/or in comparison to in vitro‐grown bacteria. Such in planta transcriptomic approaches would help identify new pathogenic behaviours and adaptation to the host during the infection process and in the different tissues colonized.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been widely used in the study of interactions between host plants and pathogens; the powdery mildew Erysiphe pisi pathogen and the host plant Medicago truncatula [ 19 ], the Xanthomonas oryzae pv. Oryzicola (Xoc) pathogen and the host plant rice [ 20 ], the Aspergillus flavus pathogen and the host plant Zea mays [ 21 ], the Xanthomonas fragaria pathogen and the host plant strawberry [ 22 ], and the Heterobasidion annosum s.l. pathogen and the host plant Norway spring [ 23 ] were sequenced by dual-seq.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the interaction transcriptome sequencing analysis at 12 and 29 days after the strawberry was infected by X. fragariae showed that the genes related to chloroplast metabolism and photosynthesis were highly expressed in the host plants in the early stage of infection, and the genes involved in host recognition and self-pathogenesis were relatively low in the pathogens in the late stage of infection. This evidence indicates the coevolution process in the interaction between pathogen and host [ 22 ]. This provides a reference and basis for the study of dual-seq in different stages of hybrid bamboo infection by Arthrinium phaeospermum .…”
Section: Introductionmentioning
confidence: 99%